2022
DOI: 10.3386/w30520
|View full text |Cite
|
Sign up to set email alerts
|

Assessing School District Decision-Making: Evidence from the COVID-19 Pandemic

Abstract: The COVID-19 pandemic drew new attention to the role of school boards in the U.S. In this paper, we examine school districts' choices of learning modality-whether and when to offer inperson, virtual, or hybrid instruction-over the course of the 2020-21 pandemic school year. The analysis takes advantage of granular weekly data on learning mode and COVID-19 cases for Ohio school districts. We show that districts respond on the margin to health risks: all else equal, a marginal increase in new cases reduces the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Houston and Steinberg (2022), however, show that when examining variation between districts within states, "counties with higher Covid case rates had lower in-person instruction rates" (p. 19). In addition, Christian et al (2022) found that in Ohio, marginal increases in a school's COVID-19 cases reduced the probability that school would be in-person the next week. Thus, earlier studies' reliance on countylevel data and national (rather than within-state) comparisons may explain why they found COVID-19 rates to be insignificant predictors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Houston and Steinberg (2022), however, show that when examining variation between districts within states, "counties with higher Covid case rates had lower in-person instruction rates" (p. 19). In addition, Christian et al (2022) found that in Ohio, marginal increases in a school's COVID-19 cases reduced the probability that school would be in-person the next week. Thus, earlier studies' reliance on countylevel data and national (rather than within-state) comparisons may explain why they found COVID-19 rates to be insignificant predictors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also focusing on districts' initial fall instructional mode decisions, DeAngelis and Makridis (2021) emphasize the influence of politics as well as how per‐pupil spending decreases and COVID‐related death rate increases correspond with in‐person instruction increases. Finally, Christian et al (2022) assess granular weekly learning mode data from Ohio public school districts and argue that, at the margins, COVID‐19 infection rates as well as decisions by peer school districts informed learning mode decisions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Both Dee et al (2021) and Oster et al (2021), by contrast, draw on the more limited Burbio learning mode data set that includes information from only 1200 US public school districts (representing 46% of kindergarten through Grade 12 schools). Similarly, while Christian et al (2022) draw from the COVID‐19 School Data Hub (CSDH, 2022) data set, their study includes only Ohio public school districts. Second, while Oster et al (2021) explore how access to in‐person learning modes varied across student groups (as well as geography and school level), their analyses, while helpful, are largely descriptive in nature.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, school districts boundaries are frequently redrawn in the United States. In the overwhelming majority of cases, this is done by a school board, a governing body made up of elected officials drawn from the local community (Land 2002;Christian, Jacob, and Singleton 2022). In densely populated portions of the country, this redistricting often involves contiguous districts "trading" portions of land under the jurisdiction of each.…”
Section: Intentionally Segregationistmentioning
confidence: 99%